Supply Chain Management Drivers and Public Policy of Private Partnership in Indonesian Higher Education Sector - Maya Puspita Dewi; Mudiyati Rahmatunnisa; Asep Sumaryana; JB Kristiadi (International Journal of Supply Chain Management, 2018)
Now a day, supply chain management (SCM) is becoming increasingly important. SCM practices have been emerged up to a great extent. However, a significant part of literature is still missing on SCM in services sector. A scarce number of research studies were focused on SCM in the academia. In rare cases any study formally documented the role of public policy for private partnership on SCM in educational institutions, particularly in Indonesia. Thus, the prime objective of this study is to investigate the role of education suppliers and research suppliers to boost up SCM in Indonesia with moderating role of public policy for private partnership. To achieve this objective, the current study used quantitative approach. Survey method used to collect the data. Data were collected from employees of Indonesian universities. Three hundred (300) questionnaires were distributed among the respondents. After analysing the data through Smart PLS 3, it was found that education suppliers and research suppliers have significant influence on SCM through universities management. Moreover, it was investigated that public policy for private partnership has moderating role between university management and SCM. Public policy for private partnership significantly enhance the positive effect of education suppliers and research suppliers on SCM. Thus, the current study contributed by investigating the mediating role of university management and moderating role of public policy for private partnership. Finally, this study investigated the major derives of SCM in educational sectors, namely; education suppliers, research suppliers, university management and public policy for private partnership.